HOURLY ROUNDING DAN PENCEGAHAN JATUH: KAJIAN EVIDENCE-BASED DALAM KONTEKS KEPERAWATAN - Azmi Sulintya Syahwa; Ari Sunari; Siti Hutami; Florencia Eny Agustin; Ratna Magdalena (Jurnal Kesehatan, 2025)
Falls are among the most frequent and serious incidents in healthcare facilities, leading to increased morbidity, mortality, length of stay, and healthcare costs. Preventing falls is therefore a major priority in patient safety. This review aimed to evaluate the effectiveness of hourly rounding (HR) as an evidence-based strategy to reduce fall rates. A narrative review was conducted across multiple quality improvement projects, quasi-experimental studies, and literature reviews that implemented HR using the 5Ps approach (pain, position, potty, possessions, pumps). Findings indicated that HR reduced fall rates by up to 55% in some studies, although not always with statistical significance. Consistent benefits included enhanced staff accountability, improved patient satisfaction, and a strengthened culture of safety. Limitations noted were small sample sizes, short implementation periods, and variability in staff adherence. Conclusion: HR is a proactive nursing strategy that contributes to safer care environments and has the potential to reduce patient falls. Further research is needed to assess long-term sustainability, larger sample sizes, and integration with multifactorial fall prevention strategies.